Intelligent Will, Causality, and Action in Hegel’s Jenaer Realphilosophie 1805/06 - Tereshchenko, Yuliia (ETHICS IN PROGRESS, 2024)
This paper introduces foundational claims originating from Hegel’s Jenaer Realphilosophie 1805/6 to Hegel’s action studies. It focuses on the concept of the minded subject whose intelligent will [als Wille, der Intelligenz ist] is essential for approaching the effective agency capable of action [das Tun; die Tätigkeit] and labor [Arbeiten]. In this work, agency is initially conceptualized in terms of its self-actualization and self-objectification in external achievements. It shows that, unlike in certain neo-Hegelian considerations, the emergence of agency and the ability to act [Handlung] freely, deliberately, purposefully, and intentionally is determined by the development of the individual human mind and its explanation does not need the entire complex socio-economic apparatus related to labor [Arbeit].